Government of Tanzania uptake joint village land use planning: tool to secure shared grazing lands across administrative borders in pastoral areas - Flintan, Fiona E.; Deus, Kalenzi; Olesikilal, Birikaa (CGIAR System Organization, 2024)
Pastoralists have poor tenure security and are often excluded from land-related decision- making processes. They are poorly equipped to protect their lands from sale or encroachment. Land use planning that maintains the integrity of the pastoral system and the rangelands on which pastoralism depends is highly complex. Developing appropriate approaches for land use planning has proved challenging for many local and national governments. Where they have been developed, implementation of VLUPs has also often been restricted due to limited funding, skills and capacities. Since 2010, the Sustainable Rangeland Management Project achieved significant progress in village land use planning. This was led by the International Land Coalition and International Fund for Agricultural Development (IFAD), with technical support from ILRI, including strengthening tools such as Participatory Rangeland Resource Mapping. A 2021 report on lessons learned from the SRMP highlighted the need for a concerted effort to include less visible groups, such as women and if JVLUP was to be scaled up, to improve the enabling environment. In 2022, the Livestock and Climate Initiative took up JVLUP to strengthen and scale it.